DETERMINANT FACTORS OF CONSUMER PREFERENCES IN INDONESIA AIRLINES INDUSTRY - Aditya Wardhana; Syahputra Syahputra; Budi Rustandi Kartawinata (Jurnal Bisnis Manajemen, 2017)
Research objectives was to find determinant  that determines the preferences of consumers in using flight services in Indonesia and knowing  factors priority preferences of consumers in using the flight in Indonesia. Research methodology used the quantitative method and technical data analysis using factor analysis .The size of the population of 91 million passengers with a target population was  commercial airlines passengers in Indonesia. The total sample using Slovin formulas on the level of confidence 95 % as many as 400 respondents. The sample collection technique using nonprobability sampling with incidental sampling method. Data collection techniques using a questionnaire, observation, and an interview. The result showed that determinant  of consumer’s preferences in using flight services in Indonesia can be grouped in three factors there were arranged based on  priority of attributes as follows: (a) tariff  consisting of a tariff as attribute, (b)  services consisting of attributes such as on-time departure and arrival, safety, reservation and chek-in convenience, airline' crews, flight patterns, cabin services, baggage services, and airplanes, and (c) image of airlines composed of airline image as attribute.